A Novel Material for High‐Performance Li–O2 Battery Separator: Polyetherketone Nanofiber Membrane. Issue 21 (23rd April 2022) - Sun, Yuxuan; Chen, Kai; Zhang, Chi; Yu, Huiting; Wang, Xue; Yang, Dongyue; Wang, Jin; Huang, Gang; Zhang, Suobo
Abstract: The properties of separators significantly affect the efficiency, stability, and safety of the lithium‐based batteries. Therefore, the improvement of the separator material is critical. Polyetherketone (PEK) has excellent general properties, such as mechanical strength, chemical stability, and thermal stability. Thus, it is expected to be an optimal separator material. However, its low solubility‐induced poor processibility makes it difficult to be used for nanoscale product manufacturing. In this work, the soluble precursor polymer is prepared by introducing a "protecting" group into monomer, and fabricated into nanofiber membrane, which can be converted into polyetherketone nanofiber membrane by a simple acid treatment. The membrane prepared by this chemical‐induced crystallization method exhibits superior chemical, thermal stability, and mechanical strength. Li–O2 batteries with the fabricated membrane as separator have a high cycling stability (194 cycles at 200 mA g −1 and 500 mAh g −1 ). This work broadens the application field of PEK and provides a potential route for battery separators. Abstract : Using a chemical‐induced crystallization strategy, the contradiction between solvent resistance and processing performance of polyetherketone (PEK) is eliminated, and a PEK nanofiber membrane is manufactured. This membrane has high mechanical properties, thermal stability, hydrophobicity, high porosity, and narrow pore size distribution. The use of PEK in high performance Li–O2 batteries proves its potential in battery separators.